Case of a Man with Hemichorea and Behavioral Changes: "A Red Herring". Issue 4 (30th March 2022) - Kleiner, Galit; Ryan, Stephen A.; Bilbao, Juan; Keith, Julia; Rogaeva, Ekaterina; Black, Sandra E.; Lang, Anthony E.; Masellis, Mario
ABSTRACT: Background: Progressive supranuclear palsy (PSP)–pallido‐nigro‐luysian atrophy (PNLA) is a neuropathological entity thought to be a variant of classic PSP. Clinical features and pathologic hallmarks are the same in both conditions; however, age and order of symptom onset, disease duration and prognosis, and distribution and density of pathology differentiate the 2 entities. Objectives: This study presents a PSP‐PNLA case confirmed pathologically with a clinical presentation of hemichorea/ballism, spasticity, progressive hemiparesis, and a frontal behavioral syndrome with relative cognitive sparing early in the disease course. Methods: We describe the clinical progression in this unique case supplemented with video and imaging findings in the form of magnetic resonance imaging and brain single photon emission computed tomography. Final diagnosis is via pathological analysis at autopsy. Results: We present an elderly gentleman who manifested a clinical syndrome consisting of subacute onset of chorea that at presentation was distinctly unilateral and a frontal behavioral syndrome in the setting of mild thrombocytopenia and elevated anticardiolipin antibodies. Positive antiphospholipid antibodies resulted in an initial antemortem diagnosis of primary antiphospholipid syndrome as a cause of his chorea. Longitudinal follow‐up over 5 years demonstrated a progression of clinical features with hemi‐motor impersistence/chorea, disinhibition and impulsivity, and eventually corticospinal distribution weakness on the initially affected side. He required nursing home care and falls necessitated wheelchair use. Postmortem neuropathological study revealed a diagnosis of frontotemporal lobar degeneration‐tau, PSP‐PNLA. Conclusions: This case broadens the phenotype of PSP‐PNLA and to our knowledge is the only case presenting with unilateral chorea.